The Linkage Between Foreign Capital Inflows and Domestic Saving in Tanzania - Joseph, Cornel (Journal of Developing Economies, 2025)
This study examines whether money from outside the country (such as remittances, foreign direct investment, and foreign aid) adds to or replaces domestic savings in Tanzania. The research uses a 33-year time series dataset (1991-2023) and employs the Autoregressive Distributed Lag (ARDL) estimation approach. Findings show that, in the long run, remittances, foreign direct investment, and foreign aid have a negative and statistically significant effect on savings in Tanzania. This means that when Tanzania gets foreign aid, remittances, and investments from outside people will save less. However, the results depict that, in the short run, foreign direct investment and remittance inflows have a positive and statistically significant effect on savings in Tanzania. Therefore, the government of Tanzania needs to develop policies that ensure that, in the long run, foreign aid, foreign direct investment and remittance inflows contribute to savings rather than replace them. Specifically, the government needs to strengthen domestic capital formation rather than relying on foreign capital. This could strengthen domestic savings and lead to economic growth in Tanzania.